Digital Transformation and Legal Certainty: Substantive Examination in Indonesian Corporate Governance - MJ. Widijatmoko; Nurchayatie, Lisza; Rusli, Radif Khotamir (JURNAL ILMIAH GEMA PERENCANA, 2026)
The digitalization of corporate legal services in Indonesia, spearheaded by the Directorate General of General Law Administration (Ditjen AHU), represents a significant bureaucratic reform. However, the convenience of self-declaration systems has raised concerns about legal certainty, leading to the implementation of a substantive examination policy for corporate data alterations. This study analyzes the implications of this policy shift, examining the tension between administrative efficiency and the imperative of legal certainty. Using a doctrinal research method, this paper investigates the legal framework, implementation challenges, and theoretical underpinnings of the substantive examination policy. The results indicate that while the policy is a necessary corrective to the vulnerabilities of the previous system, its implementation faces significant operational hurdles, including capacity constraints and procedural complexities. The discussion reasserts fundamental civil law principles, analyzes practical implementation issues, and draws lessons from comparative international models to propose a hybrid, risk-based verification framework. The conclusion argues that the long-term success of this reform depends on integrating technology to create a system that is both secure and efficient, thereby strengthening corporate governance and investor confidence in Indonesia.